Kinematics but not kinetics alterations to single-leg drop jump movements following a subject-tailored fatiguing protocol suggest an increased risk of ACL injury - Nardon, Mauro; Ferri, Umberto; Caffi, Giovanni; Bartesaghi, Manuela; Perin, Cecilia; Zaza, Antonio; Alessandro, Cristiano (Frontiers in Sports and Active Living, 2024)
Introduction. Neuromuscular fatigue causes a transient reduction of muscle force, and alters the mechanisms of motor control. Whether these alterations increase the risk of anterior cruciate ligament (ACL) injury is still debated. Here we compare the biomechanics of single-leg drop jumps before and after the execution of a fatiguing exercise, evaluating whether this exercise causes biomechanical alterations typically associated with an increased risk of ACL lesion. The intensity of the fatiguing protocol was tailored to the aerobic capacity of each participant, minimizing potential differential effects due to inter-individual variability in fitness. Methods. Twenty-four healthy male volunteers performed single leg drop jumps, before and after a single-set fatiguing session on a cycle ergometer until exhaustion (cadence: 65-70 revolutions per minute). For each participant, the intensity of the fatiguing exercise was set to 110% of the power achieved at their anaerobic threshold, previously identified by means of a cardiopulmonary exercise test. Joint angles and moments, as well as ground reaction forces (GRF) before and after the fatiguing exercise were compared for both the dominant and the non-dominant leg. Results. Following the fatiguing exercise, the hip joint was more extended (landing: Δ=-2.17°, p=0.005; propulsion: Δ=-1.83°, p=0.032) and more abducted (landing: Δ=-0.72°, p=0.01; propulsion: Δ=-1.12°, p=0.009). Similarly, the knee joint was more extended at landing (non-dominant leg: Δ=-2.67°, p<0.001; dominant: Δ=-1.4°, p=0.023), and more abducted at propulsion (both legs: Δ=-0.99°, p<0.001) and stabilization (both legs: Δ=-1.71°, p<0.001) hence increasing knee valgus. Fatigue also caused a significant reduction of vertical GRF upon landing (Δ=-0.21 N/kg, p=0.003), but not during propulsion. Fatigue did not affect joint moments significantly. Conclusion. The increased hip and knee extension, as well as the increased knee abduction we observed after the execution of the fatiguing exercise have been previously identified as risk factors for ACL injury. These results therefore suggest an increased risk of ACL injury after the execution of the participant-tailored fatiguing protocol proposed here. However, the reduced vertical GRF upon landing and the preservation of joint moments are intriguing, as they may suggest the adoption of protective strategies in the fatigued condition to be evaluated in future studied.